(untitled) (Research, Society and Development, 2020)
The presence of interferences in the seating area of ​​the removable prostheses can impair their stability at the end of the rehabilitation. Brakes, flaps and excess soft tissue are due to the resorption of the edges after extractions or due to trauma. Pre-prosthetic surgical techniques can improve the anatomical conditions of edges and vestibules, facilitating the installation of removable prostheses. The aim of this study is to address pre-prosthetic soft tissue surgery techniques in order to improve the adaptation and seating of removable prostheses, returning the patient to adequate comfort, stability, function and aesthetics. This work is based on the bibliographic search of scientific articles available through the BVS, SCIELO database, literary works and dental publications of the specialty using the library of Faculdade Patos de Minas and Google Scholar. Pre-prosthetic surgeries can be performed on both hard and soft tissue, according to the clinical need of each case and the ultimate goal is to improve the anatomical conditions for subsequent installation of total or partial removable dentures that can give the patient comfort when in function. When well indicated and planned, it allows the manufacture of more stable prostheses avoiding discomfort and injuries.